Difficulties in Teaching Biology Curricula in Secondary Education from the Perspective of Teachers in the City of Nalut, Libya - Batar, Hotaf; Afleefil, Asmaa (Sharwes Scientific Journal, 2025)
The research aimed to identify the difficulties facing teachers in teaching biology in secondary schools in Nalut city, Libya, from their point of view. The descriptive analytical approach was used, including a questionnaire tool prepared to achieve the research objectives. The questionnaire focused on 6 axes derived from previous studies. The research community consisted of all biology teachers in the city and (21) teachers responded to represent the research sample. After conducting statistical analyses, the research results showed that (3) axes obtained an average response degree, arranged in descending order as follows: the axis of difficulties related to the curriculum, then the axis of difficulties related to the student, followed by difficulties related to educational tools. As for the remaining axes, they obtained a low response degree, and they are as follows: the axis of difficulties related to teaching methods, followed by the axis of difficulties related to assessment, and finally those related to the teacher. The most prominent findings of the research are that teachers face difficulties in teaching biology in secondary schools in Nalut, the most important of which are: the lack of training courses targeting teachers, students memorizing biology without understanding it, parents not following up with their children in school, the lack of requirements for applying modern teaching methods for biology, the large content of the textbook and its unsuitability for the time allocated to it, the lack of biology laboratories and if they are available, they are not equipped in a way that meets the needs of the subject.